Effects of ProfessionalNurses’ParticipationProgrammeon Patient Management to PreventPressure UlceratPhrae Hospital - Muangmor, Malee; Daengthern, Laddawan (NU Journal of Nursing and Health Sciences, 2019)
The purposes of this quasi-experimental research were to compare the satisfaction pre and post of one group of test professional nurses and the occurrence of pressure ulcers in the medical ward, at Phrae Hospital before and after completing the programme. The research participants are comprised of 30 professional nurses who were selected by simple random sampling. The instruments were professional nurses’participation programme on patient management to prevent pressure ulcer based on Cohen and Uphoff’s theory (1980), for twelve weeks. The data collection tools were demographic questionnaires, professional nurses’satisfaction of questionnaires and a pressure ulcers recording form. The IOC was between 0.6-1.0. The reliability of the questionnaires was 0.96. The data was analyzed using frequency, percent, age mean, standard deviation and paired t-test. The results showed that:1)after undertaking the participation programme on patient management to prevent pressure ulcers, the professional nurses’ satisfaction score was statistically significantly higher (at a level of 0.0 1) than before undertaking the programme 2) after undertaking the participation programme on patient management to prevent pressure ulcers, the occurrence of pressure ulcers in the medical ward, at Phrae hospital, was reduced.